PERAN BAITUL MAL WAT TAMWIL DALAM AMAL USAHA MUHAMMADIYAH KEBAYORAN BARU - Supendi, Moh.; Maududi, Mukhlish M (Universitas Muhammadiyah Prof DR HAMKA, 2018)
The cooperative is a financial institution that is easily accessible by the community, by providing small-scale capital assistance to lower middle-class society, on the other hand, the spirit to use the Islamic financial system, making Baitul Mal Wat Tamwil become the middle ground. This research was conducted to find out the description of the role of Baitul Mal Wat Tamwil (BMT) in the Muhammadiyah Kebayoran Baru Business Charity, This research used a qualitative descriptive method, the research started from collecting secondary data and then completed with open interview data to respondent like Management and Cooperative Member Branch of Muhammadiyah Kebayoran Baru. The conclusion obtained is the role of cooperatives in very good and there is a discourse to use the system of sharia in the cooperative Sinar Surya. Keywords: Baitul Mal Wat Tamwil, Roles, Charity Business Muhammadiyah